2014
DOI: 10.1016/j.bpj.2013.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lipid Interactions on Model Vesicle Engulfment by Alveolar Macrophages

Abstract: The engulfment function of macrophages relies on complex molecular interactions involving both lipids and proteins. In particular, the clearance of apoptotic bodies (efferocytosis) is enabled by externalization on the cell target of phosphatidylserine lipids, which activate receptors on macrophages, suggesting that (local) specific lipid-protein interactions are required at least for the initiation of efferocytosis. However, in addition to apoptotic cells, macrophages can engulf foreign bodies that vary substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…The inhibition of efferocytosis by high concentrations of AC-derived EMPs together with the weaker effects of CS-derived EMPs on efferocytosis during conditions of aSMase loss of function suggest a competitive effect of EMPs with apoptotic cells for phagocyte engulfment. In addition, critical levels of ceramide in EMPs may hinder efferocytosis, which is consistent with our report that increasing ceramide content in a target lipid vesicle bilayer significantly inhibited macrophages efferocytosis, due to increased membrane stiffness and impaired intercellular membrane fusion 24 . We did detect sphingosine-1 phosphate (S1P) within cMPs (ranging from 0.83 to 1.65 pmoles/cMP in healthy to 1.02 to 2.38 pmoles/cMP in COPD individuals).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The inhibition of efferocytosis by high concentrations of AC-derived EMPs together with the weaker effects of CS-derived EMPs on efferocytosis during conditions of aSMase loss of function suggest a competitive effect of EMPs with apoptotic cells for phagocyte engulfment. In addition, critical levels of ceramide in EMPs may hinder efferocytosis, which is consistent with our report that increasing ceramide content in a target lipid vesicle bilayer significantly inhibited macrophages efferocytosis, due to increased membrane stiffness and impaired intercellular membrane fusion 24 . We did detect sphingosine-1 phosphate (S1P) within cMPs (ranging from 0.83 to 1.65 pmoles/cMP in healthy to 1.02 to 2.38 pmoles/cMP in COPD individuals).…”
Section: Discussionsupporting
confidence: 92%
“…Since the role of CS-induced EMPs has not been reported yet, we focused our investigation on their impact on specialized phagocytes. Others and we have shown that CS and ceramides decrease apoptotic cell clearance by macrophages (efferocytosis), via alterations of the cytoskeleton and impaired intercellular membranes fusion 24 . We therefore hypothesized that MPs released during CS exposure will inhibit PBMDM efferocytosis.…”
mentioning
confidence: 64%
“…587 Sphingolipids participate in the formation of different membrane structures and subcellular organelles, such as mitochondria and ER, and are also involved in the fusion and biophysical properties of cell membranes. 588 Ceramides, positioned at the core of sphingolipid metabolism, play several roles that affect multiple steps of macroautophagy, by inhibition of nutrient transporters, 589 by modulation of BCL2-BECN1 association at the level of AKT signaling, 590 and by regulation of mitophagy. 591 The latter function is regulated by a particular ceramide species, steroyl (C18:0)-ceramide, a sphingolipid generated by CERS1 (ceramide synthase 1).…”
Section: Sphingolipidsmentioning
confidence: 99%
“…Both, cholesterol-loaded vesicles, as well as their combination with SP-C, led to a higher lipid engulfment by AMs (Ruwisch et al, 2020). Increased cholesterol content, however, seemed to increase lipid uptake by AMs regardless of the presence of SP-C. Vesicle size and membrane fluidity can affect lipid uptake by AMs (Justice et al, 2014), and thus, the combined effect of cholesterol and SP-C on membrane structure and fluidity (Roldan et al, 2016(Roldan et al, , 2017 is a factor that must be taken into account. The study of the transcriptional response of MH-S cells to lipid administration revealed that genes associated to lipid metabolism and cholesterol transport were altered upon lipid uptake.…”
Section: Sp-c and Cholesterol Relationships In The Lung Surfactant Comentioning
confidence: 96%